Meta-analysis of cardiovascular outcome trials assessing the impact of glucagon-like peptide-1 receptor agonists on major cardiac arrhythmias. (14th October 2021) - Boulmpou, A; Patoulias, D; Teperikidis, E; Toumpourleka, M; Vergopoulos, S; Tsavousoglou, C; Doumas, M; Fragakis, N; Vassilikos, V; Papadopoulos, C E
Abstract: Background: Type 2 diabetes mellitus poses a significant health burden, whereas growing attention has been focused on the novel classes of antidiabetic drugs. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) constitute such a group of antidiabetic agents. In recent large, placebo-controlled randomized clinical trials (RCTs), GLP-1RAs have demonstrated beneficial cardiovascular effects. Nevertheless, the clear antiarrhythmic benefit has not been underlined yet. Purpose: The purpose of the present analysis was to clarify the impact of antidiabetic treatment with GLP-1RAs on the several different types of cardiac arrhythmias, based on data extracted from relevant cardiovascular outcome trials. Methods: We searched PubMed plus grey literature for all available cardiovascular and renal outcome, placebo-controlled RCTs utilizing GLP-1RAs versus placebo. Results: We pooled data from 7 cardiovascular outcome trials with GLP-1RAs in a total of 55, 943 randomized participants patients. When compared to placebo, treatment with GLP-1RAs did not provide a significant benefit in the risk for atrial fibrillation (RR = 0.81, 95% CI: 0.78–1.15, I 2 =51%) (Figure 1a), atrial flutter (RR=0.79, 95% CI: 0.53–1.16, I 2 =0%) (Figure 1b), ventricular fibrillation (RR=0.99, 95% CI: 0.48–2.04, I 2 =0%) (Figure 1c), ventricular tachycardia (RR=1.41, 95% CI: 0.87–2.28, I 2 =10%) (Figure 1d), atrial tachycardia (RR=0.63, 95% CI: 0.10–3.90, I 2 =24%) (Figure 2a), sinus node dysfunction (RR=0.70, 95% CI: 0.40–1.23, I 2 =0%) (Figure 2b), ventricular extrasystoles (RR=1.37, 95% CI: 0.56–3.30, I 2 =0%) (Figure 2c), second-degree atrioventricular block (RR=0.96, 95% CI: 0.52–1.74, I 2 =0%) (Figure 2d) or complete atrioventricular block (RR=0.78, 95% CI: 0.39–1.54, I 2 =38%) (Figure 2e). Conclusions: In patients with type 2 diabetes mellitus, treatment with GLP-1RAs does not significantly affect the risk for major cardiac arrhythmias. FUNDunding Acknowledgement: Type of funding sources: None.